Performance of Tobo Basampuak Dance by the Sinar Tampalo Arts Study in Nagari Padang Laweh, Koto VII District, Sijunjung Regency - Dona Evrie; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This article aims to describe and analyze the presentation form of Tobo Basampuak Dance from Nagari Padang Laweh, a dance that tells the activities of farmers when going down to the fields until harvest. The type of research is qualitative with a descriptive approach. Data collection techniques are carried out by means of literature study, observation, interviews, and documentation. The research findings show that Tobo Basampuak dance is a new creation dance that has a variety of movements such as, bararak masuk, mamangkua, malunyah, batanam, basiang, drama kobou mangoncah sawah, manyabik, maiyiak, maangin and malapeh panek and bararak keluar. Tobo Basampuak dance consists of 2 male dancers and 6 female dancers, using horizontal and curved floor designs. This dance has a dramatic design because in the middle of the performance there is a dialog by the dancer when the buffalo appears. This dance is accompanied by dendang dodou, as well as talempong, drum, gong, and gandang musical instruments. The costumes of male dancers are taluak balango clothes, galembong pants, sasampiang, and deta, while the female costumes are basiba kurung clothes, songket, and deta bacincin. The properties used consist of hoes, sickles, niru, and kambuik. Some are presented on stage and some in an open field, and are performed every year at the Lansek Manih Festival.